Relación de la digitalización de productos bancarios del Banco BBVA Perú en la ventaja competitiva en Lima Metropolitana - Piñas Talavera, Renzo Guillermo (2022)
This research aims to find the relationship between the digitization of banking products and the competitive advantage in Banco BBVA Peru, in which three specific objectives were set, finally managing to identify the benefits to which customers are exposed, such as the streamlining of processes, the main risk of the theft of information that would generate greater concern on the part of users and the rapid response to the client in the event of any inconvenience or problem they have during the processing of their procedures. The following investigation has a quantitative approach, in such a way that a problem, objectives, hypotheses and variables were raised. This type of approach offers greater credibility in the results. Likewise, the scope of the research is correlational since the research not only focuses on a single variable, but on the degree of relationship that one variable has with the other, allowing it to be evaluated and verified. For this, an exhaustive field work was carried out in which various techniques were used, such as data collection and instruments to obtain the desired results, previously a pilot test was carried out, in such a way that the correct understanding of the questions was confirmed. Starting from the two selected variables, such as competitive advantage and digitization, the target audience and the sampled public were identified, considering that the sample size to be surveyed is 151 people, this being a necessary number. This being the way in which the objectives were met and responding to the hypotheses initially raised.